Mesectodermal leiomyoma of the ciliary body: case report. Issue 1 (January 1989) - White, V; Stevenson, K; Garner, A; Hungerford, J
Abstract : The clinical, light microscopical, and electron microscopical features of a mesectodermal leiomyoma of the ciliary body are presented. This exceptionally rare and apparently benign tumour is considered to be of neural crest origin. In the case described the tumour cells were seen to contain thin filaments with focal densities and conspicuous numbers of mitochondria, and smooth muscle protein was demonstrated by immunohistochemical means.